2008
DOI: 10.1111/j.1600-0722.2008.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of digitized periapical radiographs validated against micro‐computed tomography scanning in evaluating orthodontically induced apical root resorption

Abstract: The aim of this study was to validate the use of digitized periapical radiographs in evaluating orthodontically induced apical root resorption against micro-computed tomography (micro-CT) scanning as a criterion standard test. In a standardized experimental protocol, 29 premolars in 16 subjects were tipped buccally for 8 wk. Nineteen contralateral premolars not subjected to orthodontic movement served as controls. Standardized periapical radiographs were taken before and after the experimental period (Rx metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 38 publications
0
32
0
2
Order By: Relevance
“…Micro-computed tomography (micro-CT) analysis is the current gold standard for the quantification of RR. 4 OIRR is a multifactorial problem that can occur as the result of a combination of individuals' biological variabilities, genetic predisposition, and orthodontic mechanical factors. 5 Torque force induces bucco-lingual rotation of the tooth, 6 and it has been identified as one of the major risk factors for OIRR.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-computed tomography (micro-CT) analysis is the current gold standard for the quantification of RR. 4 OIRR is a multifactorial problem that can occur as the result of a combination of individuals' biological variabilities, genetic predisposition, and orthodontic mechanical factors. 5 Torque force induces bucco-lingual rotation of the tooth, 6 and it has been identified as one of the major risk factors for OIRR.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggested that the diagnosis of ERR using PR could be highly inaccurate. 9 In recent years, cone-beam computed tomography (CBCT) has been widely applied in dental clinics because it enables dental practitioners to visualize the three-dimensional (3D) data and eliminates the structural superimposition. 10 However, the expenses and radiation of CBCT are significantly higher than that of PR.…”
Section: Introductionmentioning
confidence: 99%
“…Although tomographic tests have a greater resolution and adequately image software analyses, radiographic tests have a similar efficacy for surgery follow-up (Ferrús-Torres et al, 2009). Thus, this research used periapical radiographies because they have a better distortion when compared to other radiographic tests (Dudic et al, 2008) besides providing diagnostic efficacy.…”
Section: Discussionmentioning
confidence: 99%